NON-TRIVIALITY OF THE RESULTS OF MILGRAM FIELD EXPERIMENT IN MOSCOW AND NEW YORK SUBWAY - Mitina, O.V.; Voronov, A.Y. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
Non-triviality of the results of the field experiment conducted on Stanley Milgram’s methodology in the New York and Moscow subway have been studied. The statistical significance of the difference between empirical and predicted results has been taken as the non-triviality criterion. 208 respondents (psychologists and students studying psychology) were asked to predict an experimental result in dependence on an experimenter’s and subject’s gender, a subject’s age, and a city where the experiment was carried out. The obtained results have confirmed our hypothesis on non-triviality of the experiments in subways: it has been showed that there is a statistically significant difference between real behavior of subway passengers (in New York and in Moscow) and predictions made by Moscow and Tashkent respondents. Practically in most cases the predicted probability that a subject gives a seat after request of experimenter (young woman or young man) is much less than in reality. The structural equation modeling (SEM) has been used to analyze the data by constructing the model taking account of all factors mentioned above. The model fit the experimental data well (CFI = 0.919). It has been found that predicted results depend not only on gender, age, and residence of a respondent but also on the degree of familiarity with the research. The obtained data give an important material for a further study of the role of situational (an experiment design) and individual (respondent characteristics) factors in predicted results; they contribute to further understanding of the problem of creation and support of non-formal social norms in various cultures and show new aspects of research carried out on experimental methodology of Stanley Milgram.